Preparation method and application of core-shell structure conductive hydrogel electronic skin

CN122941027APending Publication Date: 2026-10-20SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611374787.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了解决现有水凝胶材料导电性、抗冻性、力学性能、粘附性和抗疲劳性能较差的问题

Benefits of technology

(1)本发明提供的水凝胶选用环保型交联剂乙二醇二甲基丙烯酸酯,采用自由基聚合工艺制备化学交联网络的聚丙烯酸基水凝胶电子皮肤,摒弃物理交联效率低、网络结构不稳定的缺陷,实现水凝胶的高效可控固化,所得水凝胶电子皮肤具有优异的力学性能和抗疲劳性能,其拉伸强度达到1.798MPa,断裂伸长率达到700%,在500%应变下循环拉伸10次后,拉伸强度仍能达到1.2MPa。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1788751264984-000002
    Figure REF-OBJ-1788751264984-000002
  • Figure REF-OBJ-1788751264984-000003
    Figure REF-OBJ-1788751264984-000003
  • Figure REF-OBJ-1788751264984-000004
    Figure REF-OBJ-1788751264984-000004
Patent Text Reader

Abstract

This invention discloses a method for preparing a core-encapsulated conductive hydrogel electronic skin and its application, relating to the technical field of conductive hydrogels. An antifreeze agent, acrylic acid solution, and lithium bis(trifluoromethanesulfonyl)imide dispersion are mixed, and a chemical crosslinking agent and initiator are added. The mixture is stirred until homogeneous to obtain a first prepolymer. The first prepolymer is then subjected to free radical polymerization to obtain a sensing core layer. An antifreeze agent, acrylic acid solution, and zinc trifluoromethanesulfonate dispersion are mixed, and a chemical crosslinking agent and initiator are added. The mixture is stirred until homogeneous to obtain a second prepolymer. The second prepolymer is then coated onto the sensing core layer and subjected to free radical polymerization to obtain the hydrogel electronic skin. The strong electrolytes lithium bis(trifluoromethanesulfonyl)imide and zinc trifluoromethanesulfonate are introduced into the hydrogel system, and the process is carried out via Li… + Zn 2+ The efficient ion transport network constructed by plasma synergistic migration and the high dissociation ability of sulfonic acid groups significantly improves conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of conductive hydrogels, specifically a method for preparing and applying a core-encapsulated conductive hydrogel electronic skin. Background Technology

[0002] Conductive hydrogels are a class of functional soft materials that combine high water content, a three-dimensional network structure, and electrical conductivity. They are typically composed of a hydrophilic polymer backbone and a conductive medium (such as conductive polymers, carbon-based fillers, or metal ions). Due to their excellent stretchability, structural flexibility, biocompatibility, and real-time signal transmission capabilities, conductive hydrogels are considered ideal carrier materials for constructing flexible wearable strain sensors, electronic skin, and human-computer interfaces. Electronic skin, as an artificial electronic device capable of simulating the tactile sensation of human skin, places stringent requirements on the mechanical compliance, sensing sensitivity, long-term wear stability, and adaptability to complex environments of materials. Therefore, conductive hydrogels exhibit unique advantages in this field and have attracted widespread attention. In recent years, electronic skin based on conductive hydrogels has shown extremely broad application prospects in areas such as human motion monitoring, health and medical diagnosis, and non-invasive physiological information tracking.

[0003] Although conductive hydrogels have been explored in the field of electronic skin sensing, they still face multiple challenges in practical applications, making it difficult to meet the high standards of comprehensive performance required by electronic skin. First, most hydrogels have simple preparation processes and limited functional designs, resulting in insufficient mechanical strength, conductivity stability, and self-adhesion, making it difficult to achieve stable and continuous tactile signal acquisition under conditions where electronic skin is in long-term contact with the skin. Second, electronic skin inevitably endures repeated bending, stretching, and other cyclic mechanical loads during use. Under such long-term fatigue, the three-dimensional network of hydrogels is prone to micro-cracks and structural damage, leading to a decline in mechanical properties and interruption of conductive pathways, severely affecting the sensing reliability and lifespan of the electronic skin. Furthermore, electronic skin needs to adapt to different climatic conditions. Hydrogels, with water as the main dispersion medium, typically have a freezing point below zero degrees Celsius. In cold environments or outdoor scenarios, internal water phase crystallization leads to material embrittlement and hindered ion migration, resulting in a sharp drop in conductivity or even complete failure, greatly limiting the practical usability of electronic skin in a wide temperature range.

[0004] To address the aforementioned issues, researchers have explored various modification strategies, such as constructing dual-network structures, introducing nanofillers, or adding functional components, aiming to improve the overall performance of hydrogels and advance their development into practical electronic skin. While these methods have improved certain aspects of hydrogel performance to some extent, significant limitations remain. Firstly, most modification strategies tend to focus on optimizing a single performance, which can easily lead to the deterioration of other key properties while improving one, making it difficult to achieve a synergistic improvement in the multiple indicators required for electronic skin, such as mechanical properties, conductivity, antifreeze properties, and adhesion. Secondly, existing methods largely concentrate on the regulation and compounding of chemical components, lacking a systematic solution from a microstructural design perspective. This makes it difficult to effectively overcome the contradictions between various properties, hindering the overall performance leap of electronic skin.

[0005] Therefore, how to achieve a synergistic improvement in the mechanical properties, conductivity, freeze resistance, and fatigue resistance of conductive hydrogels through ingenious structural innovation rather than solely relying on complex chemical formulations has become a core technical challenge that urgently needs to be overcome in this field, and a key bottleneck in promoting the transition of electronic skin from the laboratory to practical applications. Against this backdrop, the construction of conductive hydrogel electronic skin with core-shell functional partitions based on a "core-shell" structure design provides a new approach to breaking the aforementioned performance constraints—through the functional division and interfacial synergy between the core and shell layers, it is expected to simultaneously achieve mechanical durability and wide-temperature-range environmental adaptability, thereby advancing the progress of conductive hydrogel electronic skin in practical applications. Summary of the Invention

[0006] The purpose of this invention is to address the problems of poor conductivity, freeze resistance, mechanical properties, adhesion, and fatigue resistance in existing hydrogel materials. This invention proposes a method for preparing and applying a core-coated conductive hydrogel electronic skin. The specific technical solution is as follows: A method for preparing a core-encapsulated conductive hydrogel electronic skin, the method comprising: Lithium bis(trifluoromethanesulfonyl)imide was added to deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 58% to 62%. Antifreeze, acrylic acid solution and lithium bis(trifluoromethanesulfonylimide) dispersion were mixed in a certain proportion and ultrasonically dispersed to obtain the first mixture. Add a chemical cross-linking agent to the first mixture, stir to dissolve, and obtain the second mixture; Add an initiator to the second mixture and stir until homogeneous to obtain the first prepolymer solution; The first prepolymer liquid is injected into the mold and heated in an oven to obtain the sensing core layer; Zinc trifluoromethanesulfonate was added to deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 68% to 72%. The antifreeze, acrylic acid solution and zinc trifluoromethanesulfonate dispersion were mixed in a certain proportion and then ultrasonically dispersed to obtain a third mixture. Add a chemical cross-linking agent to the third mixture, stir to dissolve, and obtain the fourth mixture; Add an initiator to the fourth mixture and stir until homogeneous to obtain the second prepolymer solution; The sensing core layer is placed in a mold, a second prepolymer liquid is injected into the mold, and the mold is heated in an oven to obtain a core-coated conductive hydrogel electronic skin.

[0007] Preferably, the antifreeze agent is ethylene glycol, the chemical crosslinking agent is ethylene glycol dimethacrylate, the initiator is potassium persulfate, and the mass fraction of the acrylic acid solution is 54% to 56%.

[0008] Preferably, in the step of mixing the antifreeze, acrylic solution and lithium bis(trifluoromethanesulfonyl)imide dispersion in a certain proportion, the mass ratio of the antifreeze, acrylic solution and lithium bis(trifluoromethanesulfonyl)imide dispersion is 1:2.7:(0.3-1.5).

[0009] Preferably, in the step of adding a chemical crosslinking agent to the first mixture, the amount of chemical crosslinking agent added is 0.05% to 0.15% of the first mixture; in the step of adding an initiator to the second mixture, the amount of initiator added is 0.05% to 0.15% of the first mixture.

[0010] Preferably, in the step of injecting the first prepolymer liquid into the mold and heating it in an oven to obtain the sensing core layer, the oven temperature is 65°C and the heating time is 1 hour, so that the thickness of the sensing core layer after heating is 1.2 mm to 1.4 mm.

[0011] Preferably, in the step of mixing the antifreeze, acrylic solution and zinc trifluoromethanesulfonate dispersion in a certain proportion, the mass ratio of the antifreeze, acrylic solution and zinc trifluoromethanesulfonate dispersion is 1:3.5:(0.5-1.2).

[0012] Preferably, in the step of adding a chemical crosslinking agent to the third mixture, the amount of chemical crosslinking agent added is 0.03% to 0.06% of the mass of the third mixture; in the step of adding an initiator to the fourth mixture, the amount of initiator added is 0.05% to 0.1% of the mass of the third mixture.

[0013] Preferably, in the step of placing the sensing core layer into a mold, injecting a second prepolymer liquid into the mold, and heating it in an oven to obtain a core-coated conductive hydrogel electronic skin, the oven temperature is 80°C and the heating time is 2 hours, so that the thickness of the electronic skin obtained after heating is 2 mm to 2.3 mm.

[0014] An application of a core-encapsulated conductive hydrogel electronic skin as a sensor, wherein the electronic skin is prepared by the method described in any one of claims 1 to 8.

[0015] The beneficial technical effects of this invention are as follows: (1) The hydrogel provided by the present invention uses environmentally friendly crosslinking agent ethylene glycol dimethacrylate and prepares a chemically crosslinked network polyacrylic acid-based hydrogel electronic skin by free radical polymerization process. It overcomes the defects of low physical crosslinking efficiency and unstable network structure, and realizes efficient and controllable curing of hydrogel. The resulting hydrogel electronic skin has excellent mechanical properties and fatigue resistance. Its tensile strength reaches 1.798 MPa and its elongation at break reaches 700%. After 10 cycles of cyclic stretching at 500% strain, the tensile strength can still reach 1.2 MPa.

[0016] (2) The hydrogel electronic skin provided by this invention introduces the strong electrolytes lithium bis(trifluoromethanesulfonylimide) and zinc trifluoromethanesulfonate into the hydrogel system, and utilizes Li + Zn 2+ The efficient ion transport network constructed by plasma synergistic migration and the high dissociation ability of sulfonic acid groups significantly improves conductivity, and the hydrogel electronic skin achieves a conductivity of 2.212 S / m at room temperature.

[0017] (3) The hydrogel electronic skin provided by the present invention has good antifreeze properties. The addition of ethylene glycol makes the conductivity of the electronic skin reach 1.659S / m at a low temperature of -30℃, while maintaining good flexibility, thus broadening its application range in low temperature environments. Attached Figure Description

[0018] Figure 1 The diagram shown is a flowchart of a preparation method according to one embodiment of the present invention; Figure 2 Infrared spectra of the hydrogel electronic skin in Embodiment 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention; Figure 3 The images show X-ray diffraction (XRD) patterns of the hydrogel electronic skin in Examples 1, 2, 3, 4, 5 and Comparative Example 1 of this invention. Figure 4 This is a scanning electron microscope (SEM) image of the hydrogel electronic skin in Example 1 of the present invention; Figure 5 The cyclic loading-unloading curve and corresponding energy dissipation diagram under 500% strain in Embodiment 1 of the present invention are shown. Figure 6Differential scanning thermal (DSC) images of the hydrogel electronic skins of Examples 1, 2, 3, 4, 5, Comparative Examples 1, 2, and 3 of the present invention; Figure 7 The hydrogel electronic skin used in Embodiment 1 of the present invention is used to measure the change in relative resistance of a wearable strain sensor during periodic bending of the finger joints; Figure 8 The hydrogel electronic skin used in Embodiment 1 of the present invention is used to measure the change in relative resistance of a wearable strain sensor during periodic bending of the wrist joint; Figure 9 The hydrogel electronic skin used in Embodiment 1 of the present invention is used to measure the change in relative resistance of a wearable strain sensor during periodic bending of the elbow joint; Figure 10 The hydrogel electronic skin used in Embodiment 1 of the present invention is used to measure the change in relative resistance of a wearable strain sensor during periodic bending of the cervical joint; Figure 11 The hydrogel electronic skin used in Embodiment 1 of the present invention is used to measure the change in relative resistance of a wearable strain sensor during periodic bending of the knee joint; Figure 12 The hydrogel electronic skin used in Embodiment 1 of the present invention is used to measure the change in relative resistance of a wearable strain sensor during periodic swallowing. Detailed Implementation

[0019] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0020] like Figure 1 As shown, a method for preparing a core-encapsulated conductive hydrogel electronic skin includes: Lithium bis(trifluoromethanesulfonyl)imide was added to deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 58% to 62%. Antifreeze, acrylic acid solution and lithium bis(trifluoromethanesulfonylimide) dispersion were mixed in a certain proportion and ultrasonically dispersed to obtain the first mixture. Add a chemical cross-linking agent to the first mixture, stir to dissolve, and obtain the second mixture; Add an initiator to the second mixture and stir until homogeneous to obtain the first prepolymer solution; The first prepolymer liquid is injected into the mold and heated in an oven to obtain the sensing core layer; Zinc trifluoromethanesulfonate was added to deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 68% to 72%. The antifreeze, acrylic acid solution and zinc trifluoromethanesulfonate dispersion were mixed in a certain proportion and then ultrasonically dispersed to obtain a third mixture. Add a chemical cross-linking agent to the third mixture, stir to dissolve, and obtain the fourth mixture; Add an initiator to the fourth mixture and stir until homogeneous to obtain the second prepolymer solution; The sensing core layer is placed in a mold, a second prepolymer liquid is injected into the mold, and the mold is heated in an oven to obtain a core-coated conductive hydrogel electronic skin.

[0021] In this application, both lithium bis(trifluoromethanesulfonylimide) and zinc trifluoromethanesulfonate are strong electrolytes. By adding ethylene glycol and strong electrolytes to an acrylic acid solution to form a mixture, and then adding a crosslinking agent and an initiator to the mixture, the addition of ethylene glycol enables the hydrogel to operate normally at a low temperature of -30°C, greatly expanding the working range of the hydrogel electronic skin. The addition of strong electrolytes can significantly improve the conductivity and mechanical properties of the hydrogel electronic skin, expanding the applicable scenarios of the hydrogel electronic skin.

[0022] In this application, the mass ratio of ethylene glycol antifreeze, acrylic acid solution, and lithium bis(trifluoromethanesulfonylimide) dispersion is 1:2.7:(0.3-1.5), the amount of chemical crosslinking agent added is 0.05% to 0.15% of the first mixture, and the amount of initiator added is 0.05% to 0.15% of the first mixture.

[0023] In this application, the first prepolymer liquid is injected into a mold and placed in an oven for heating. The oven temperature is 65°C and the heating time is 1 hour. The thickness of the sensing core layer after heating is controlled to be 1.2 mm to 1.4 mm.

[0024] In this application, the mass ratio of the antifreeze, acrylic solution, and zinc trifluoromethanesulfonate dispersion is 1:3.5:(0.5-1.2). The amount of chemical crosslinking agent added is 0.03% to 0.06% of the mass of the third mixture, and the amount of initiator added is 0.05% to 0.1% of the mass of the third mixture.

[0025] In this application, a second prepolymer liquid is injected into a mold, which is then placed in an oven and heated at 80°C for 2 hours. The thickness of the electronic skin obtained after heating is controlled to be 2 mm to 2.3 mm.

[0026] The conductive hydrogel electronic skin with a core-encapsulated structure provided by this invention can be used in wearable strain sensors to accurately monitor human joint movements and minute physiological signals.

[0027] Example 1

[0028] 4.9 g of lithium bis(trifluoromethanesulfonyl)imide was added to 2.1 g of deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 70%. Take 19.6g of acrylic acid and 16.3g of deionized water to prepare an acrylic acid solution. Add 9.79g of ethylene glycol antifreeze and 4.29g of lithium bis(trifluoromethanesulfonyl)imide dispersion to the acrylic acid solution and ultrasonically disperse to form a uniform first mixture. Add 0.033g of ethylene glycol dimethacrylate chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.033g of potassium persulfate initiator, stir evenly to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and heated in a 65°C oven to allow the first prepolymer liquid to undergo free radical polymerization for 1 hour, thus obtaining the sensing core layer of the hydrogel electronic skin. 7.2g of zinc trifluoromethanesulfonate was added to 4.8g of deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 60%. 18.2g of acrylic acid was mixed with 15.2g of deionized water to obtain an acrylic acid solution. 9.1g of ethylene glycol antifreeze and 7.5g of zinc trifluoromethanesulfonate dispersion were added to the acrylic acid solution and ultrasonically dispersed to obtain a uniform third mixture. Add 0.018g of chemical crosslinking agent to the third mixture, stir to dissolve, then add 0.03g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid is injected into a mold containing the sensing core layer and heated in an 80°C oven. During the heating process, the second prepolymer liquid undergoes free radical polymerization for 2 hours to obtain a core-encapsulated conductive hydrogel electronic skin.

[0029] Example 2

[0030] 4.9 g of lithium bis(trifluoromethanesulfonyl)imide was added to 2.1 g of deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 70%. Take 19.6g of acrylic acid and 16.3g of deionized water to prepare an acrylic acid solution. Add 9.79g of ethylene glycol antifreeze and 4.29g of lithium bis(trifluoromethanesulfonyl)imide dispersion to the acrylic acid solution and ultrasonically disperse to form a uniform first mixture. Add 0.058g of ethylene glycol dimethacrylate chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.058g of potassium persulfate initiator, stir evenly to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and heated in a 65°C oven to allow the first prepolymer liquid to undergo free radical polymerization for 1 hour, thus obtaining the sensing core layer of the hydrogel electronic skin. 7.2g of zinc trifluoromethanesulfonate was added to 4.8g of deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 60%. 18.2g of acrylic acid was mixed with 15.2g of deionized water to obtain an acrylic acid solution. 9.1g of ethylene glycol antifreeze and 7.5g of zinc trifluoromethanesulfonate dispersion were added to the acrylic acid solution and ultrasonically dispersed to obtain a uniform third mixture. Add 0.32g of chemical crosslinking agent to the third mixture, stir to dissolve, then add 0.053g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid is injected into a mold containing the sensing core layer and heated in an 80°C oven. During the heating process, the second prepolymer liquid undergoes free radical polymerization for 2 hours to obtain a core-encapsulated conductive hydrogel electronic skin.

[0031] Example 3

[0032] 4.9 g of lithium bis(trifluoromethanesulfonyl)imide was added to 2.1 g of deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 70%. Take 20.82g of acrylic acid and 17.35g of deionized water to prepare an acrylic acid solution. Add 10.41g of ethylene glycol antifreeze and 1.42g of lithium bis(trifluoromethanesulfonyl)imide dispersion to the acrylic acid solution and ultrasonically disperse to form a uniform first mixture. Add 0.035g of ethylene glycol dimethacrylate chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.035g of potassium persulfate initiator, stir evenly to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and heated in a 65°C oven to allow the first prepolymer liquid to undergo free radical polymerization for 1 hour, thus obtaining the sensing core layer of the hydrogel electronic skin. 7.2g of zinc trifluoromethanesulfonate was added to 4.8g of deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 60%. 20.36g of acrylic acid was mixed with 16.97g of deionized water to obtain an acrylic acid solution. 10.18g of ethylene glycol antifreeze and 2.94g of zinc trifluoromethanesulfonate dispersion were added to the acrylic acid solution and ultrasonically dispersed to obtain a uniform third mixture. Add 0.02g of chemical crosslinking agent to the third mixture, stir to dissolve, then add 0.034g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid is injected into a mold containing the sensing core layer and heated in an 80°C oven. During the heating process, the second prepolymer liquid undergoes free radical polymerization for 2 hours to obtain a core-encapsulated conductive hydrogel electronic skin.

[0033] Example 4

[0034] 4.9 g of lithium bis(trifluoromethanesulfonyl)imide was added to 2.1 g of deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 70%. Take 20.2g of acrylic acid and mix it with 16.84g of deionized water to prepare an acrylic acid solution. Add 10.1g of ethylene glycol antifreeze and 2.86g of lithium bis(trifluoromethanesulfonyl)imide dispersion to the acrylic acid solution and disperse it by ultrasonication to form a uniform first mixture. Add 0.034g of ethylene glycol dimethacrylate chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.034g of potassium persulfate initiator, stir evenly to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and heated in a 65°C oven to allow the first prepolymer liquid to undergo free radical polymerization for 1 hour, thus obtaining the sensing core layer of the hydrogel electronic skin. 7.2g of zinc trifluoromethanesulfonate was added to 4.8g of deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 60%. 19.29g of acrylic acid was mixed with 16.07g of deionized water to obtain an acrylic acid solution. 9.634g of ethylene glycol antifreeze and 5g of zinc trifluoromethanesulfonate dispersion were added to the acrylic acid solution and ultrasonically dispersed to obtain a uniform third mixture. Add 0.019g of chemical crosslinking agent to the third mixture, stir to dissolve, then add 0.032g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid is injected into a mold containing the sensing core layer and heated in an 80°C oven. During the heating process, the second prepolymer liquid undergoes free radical polymerization for 2 hours to obtain a core-encapsulated conductive hydrogel electronic skin.

[0035] Example 5

[0036] 4.9 g of lithium bis(trifluoromethanesulfonyl)imide was added to 2.1 g of deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 70%. Take 18.98g of acrylic acid and 15.82g of deionized water to prepare an acrylic acid solution. Add 9.49g of ethylene glycol antifreeze and 5.71g of lithium bis(trifluoromethanesulfonyl)imide dispersion to the acrylic acid solution and ultrasonically disperse to form a uniform first mixture. Add 0.032g of ethylene glycol dimethacrylate chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.032g of potassium persulfate initiator, stir evenly to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and heated in a 65°C oven to allow the first prepolymer liquid to undergo free radical polymerization for 1 hour, thus obtaining the sensing core layer of the hydrogel electronic skin. 7.2g of zinc trifluoromethanesulfonate was added to 4.8g of deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 60%. 17.14g of acrylic acid was mixed with 14.29g of deionized water to obtain an acrylic acid solution. 8.57g of ethylene glycol antifreeze and 10g of zinc trifluoromethanesulfonate dispersion were added to the acrylic acid solution and ultrasonically dispersed to obtain a uniform third mixture. Add 0.017g of chemical crosslinking agent to the third mixture, stir to dissolve, then add 0.029g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid is injected into a mold containing the sensing core layer and heated in an 80°C oven. During the heating process, the second prepolymer liquid undergoes free radical polymerization for 2 hours to obtain a core-encapsulated conductive hydrogel electronic skin.

[0037] Comparative Example 1 27.3g of acrylic acid and 22.7g of deionized water were mixed and ultrasonically dispersed to form a uniform first mixture; Add 0.046g of chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.046g of initiator and stir until homogeneous to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and placed in a 65°C oven for free radical polymerization. After polymerization for 1 hour, the sensing core layer of the hydrogel electronic skin was obtained. Mix 27.3g of acrylic acid and 22.7g of deionized water, and then ultrasonically disperse to form a homogeneous second mixture; Add 0.027g of chemical crosslinking agent to the second mixture, stir to dissolve, then add 0.046g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid was injected into a mold containing the sensing core layer and placed in an 80°C oven for free radical polymerization. After polymerization for 2 hours, the conductive hydrogel electronic skin of Comparative Example 1 was obtained.

[0038] Comparative Example 2 Mix 21.4g of acrylic acid and 17.9g of deionized water solution, add 10.7g of ethylene glycol antifreeze to the mixture, and ultrasonically disperse to form a uniform first mixture; Add 0.036g of chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.036g of initiator and stir until homogeneous to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and placed in a 65°C oven for free radical polymerization. After polymerization for 1 hour, the sensing core layer of the hydrogel electronic skin was obtained. Mix 21.4g of acrylic acid and 17.9g of deionized water, add 10.7g of ethylene glycol antifreeze to the mixture, and ultrasonically disperse to form a uniform second mixture; Add 0.036g of chemical crosslinking agent to the second mixture, stir to dissolve, then add 0.036g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid was injected into a mold containing the sensing core layer and placed in an 80°C oven for free radical polymerization. After polymerization for 2 hours, the conductive hydrogel electronic skin of Comparative Example 2 was obtained.

[0039] Comparative Example 3 4.9 g of lithium bis(trifluoromethanesulfonyl)imide was added to 2.1 g of deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 70%. Add 9.94g of ethylene glycol antifreeze and 3.63g of lithium bis(trifluoromethanesulfonyl)imide dispersion to a mixed solution of 19.87g of acrylic acid and 16.56g of deionized water, and ultrasonically disperse to form a uniform first mixture; Add 0.033g of chemical crosslinking agent to the first mixture, stir to dissolve, then add 0.033g of initiator and stir until homogeneous to obtain the first prepolymer solution; The first prepolymer liquid was injected into the mold and placed in a 65°C oven for free radical polymerization. After polymerization for 1 hour, the sensing core layer of the conductive hydrogel electronic skin was obtained. 7.2g of zinc trifluoromethanesulfonate was added to 4.8g of deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 60%. Add 9.34g of ethylene glycol antifreeze and 6.43g of zinc trifluoromethanesulfonate dispersion to a mixed solution of 18.67g of acrylic acid and 15.56g of deionized water, and ultrasonically disperse to form a uniform second mixture; Add 0.019g of chemical crosslinking agent to the second mixture, stir to dissolve, then add 0.031g of initiator and stir until homogeneous to obtain the second prepolymer solution; The second prepolymer liquid was injected into a mold containing the sensing core layer and placed in an 80°C oven for free radical polymerization. After polymerization for 2 hours, the conductive hydrogel electronic skin of Comparative Example 3 was obtained.

[0040] Fourier transform infrared spectroscopy was performed on the core-encapsulated conductive hydrogel electronic skins prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. The test results are shown in [Figure 1]. Figure 2 X-ray diffraction tests were performed on the core-shell conductive hydrogel electronic skins prepared in Examples 1, 2, 3, 4, 5, and Comparative Example 1. The results are shown in the figure. Figure 3 The conductive hydrogel electronic skin with a core-shaped structure prepared in Example 1 was subjected to scanning electron microscopy (SEM) testing. The results are shown in [Figure 1]. Figure 4 .in Figure 2 The infrared spectrum shows that the core-encapsulated conductive hydrogel electronic skin was successfully prepared. Figure 3 The figure shows the XRD pattern. In the figure, Examples 1, 2, 3, 4 and 5 show characteristic peaks at 20.74°, while Comparative Example 1 does not show obvious characteristic peaks. This indicates that the strong electrolyte dispersion has good dispersibility in the prepared hydrogel and there is no large-area accumulation or agglomeration. Figure 4 The SEM image shows that the hydrogel network has a high degree of cross-linking and good density.

[0041] Experimental Example 1 1. Mechanical property testing The hydrogels prepared in Examples 1, 2, 3, 4, 5, Comparative Examples 1, 2, and 3 were subjected to tensile property tests, and the test results are shown in Table 1. The prepared hydrogel electronic skins were tested using a universal tensile testing machine (CMT6104). The hydrogel electronic skins were all dumbbell-shaped, with a length of 30 mm, a width of 4 mm, and a thickness of 2 mm. The tensile rate was 20 mm / min, and the test temperature was room temperature (25°C). Simultaneously, the hydrogel prepared in Example 1 was subjected to a cyclic loading and unloading test under 500% strain. The energy dissipation corresponding to the test results is shown in Table 1. Figure 5 As shown. The formula for calculating the stress-strain curve is as follows:

[0042] Where 𝜀 is the tensile strain, L is the maximum tensile length of the hydrogel, and L0 is the initial length of the hydrogel.

[0043]

[0044] Where σ is the tensile stress, F is the applied load, and A0 is the cross-sectional area of ​​the sample.

[0045] As shown in Table 1, Example 1 exhibits a tensile strength of 1.798 MPa and an elongation at break of 700%, demonstrating excellent mechanical properties. In contrast, Comparative Example 1 shows poor mechanical properties (tensile strength of 0.328 MPa and elongation at break of 426%), while Comparative Examples 2 and 3 have elongations at break of 936% and 871%, respectively, with tensile strengths of only 0.653 MPa and 0.825 MPa, respectively. Figure 5 It can be seen that after 10 cycles of loading and unloading at 500% strain in Example 1, the dissipated energy decreased from the initial 0.56 MJ / m 3 Reduced to 0.1 MJ / m 3 Furthermore, the tensile strength of the hydrogel electronic skin can still be maintained above 1.2 MPa, indicating that the hydrogel electronic skin has good stability and fatigue resistance.

[0046] Table 1. Tensile properties test results of the prepared hydrogels

[0047] Experiment Example 2 2. Antifreeze performance test The hydrogel electronic skins (6-10 mg) prepared in Examples 1, 2, 3, 4, 5, Comparative Examples 1, 2, and 3 were placed in a differential scanning calorimeter (DSC822e, Switzerland) and cooled from 20°C to -70°C at a rate of 2°C / min under nitrogen protection. The test results are shown in [Figure number missing]. Figure 6 .

[0048] according to Figure 6 It can be seen that Comparative Example 1 shows a sharp crystallization peak at -18.8℃, Example 5 shows a crystallization peak at -39.5℃, while the hydrogel electronic skins prepared in Examples 1, 2, 3, 4, Comparative Example 2 and Comparative Example 3 do not show obvious crystallization peaks at -70℃ to 20℃, indicating that the hydrogel electronic skin prepared by the present invention has good antifreeze properties.

[0049] Experimental Example 3 3. Conductivity test The room-temperature conductivity of the hydrogel electronic skins prepared in Examples 1, 2, 3, 4, 5, and Comparative Example 3 was tested using an electrochemical workstation (CHI600E / 700E). All hydrogel materials were elongated strips measuring 30mm × 10mm × 2mm. The prepared hydrogel electronic skin materials were placed in a -30℃ freezer for 24 hours before being removed and their low-temperature conductivity was tested. The results are shown in Table 2. Simultaneously, the hydrogel of Example 1 before and after freezing was connected in series with a red LED and a DC power supply to form a closed circuit, and the change in LED brightness was observed. The experiment showed that, under identical conditions except for temperature differences, the LED emitted bright red light, but the frozen hydrogel bulb dimmed. Although temperature has a certain influence on conductivity, Example 1 still exhibits good conductivity at low temperatures. The formula for calculating conductivity is as follows:

[0050] Where σ is the conductivity, R is the resistance, L is the distance between the two electrodes, and S is the cross-sectional area of ​​the hydrogel.

[0051] Table 2. Test results of the electrical conductivity of the prepared hydrogel.

[0052] As shown in Table 2, the conductivity of Example 1 is 2.212 S / m, and even after freezing at -30°C, the conductivity remains at 1.659 S / m. With increasing content of the strong electrolyte dispersion, the conductivity at room temperature gradually increases, but the decrease in conductivity at low temperatures gradually widens. Comparative Example 3 has a lower conductivity of 1.843 S / m, but its low-temperature conductivity remains stable at 1.198 S / m, indicating that the hydrogel electronic skin prepared by this invention has good electrical conductivity.

[0053] Experiment Example 4 4. Adhesion performance test Adhesion tests were conducted on Examples 1, 2, 3, 4, 5, Comparative Examples 1, 2, and 3. The samples were elongated strips with dimensions of 30 mm × 8 mm × 2 mm, and the stretching speed was 20 mm / min. The initial adhesion area was 8 mm × 14 mm. The adhesion strength is shown in Table 3.

[0054] As shown in Table 3, the adhesion strength of Example 1 is generally higher than that of other hydrogels. The adhesion strength of Example 1 with plastic and pigskin is 65 kPa and 58 kPa, respectively, while the adhesion strength of Comparative Example 2 with plastic and pigskin is 72 kPa and 68 kPa, and that of Comparative Example 3 is only 52 kPa and 47 kPa. This indicates that Example 1 has good adhesion and ensures that it can adhere stably to the skin surface.

[0055] Table 3. Test results of the adhesion properties of the prepared hydrogel

[0056] Experimental Example 5 5. Sensor performance test Samples from Example 1, measuring 40mm × 10mm × 2mm, were attached to the finger joints, wrist joints, elbow joints, neck joints, knee joints, and throat. Both ends were connected to an electrochemical workstation. Human movement was monitored by measuring the change in the relative resistance of the hydrogel as a function of joint movement. The formula for calculating the resistance change is as follows:

[0057] Where R0 is the resistance of the hydrogel when no strain is applied; R x It is the resistance of the hydrogel after strain is applied.

[0058] Figure 7 The change in relative resistance during periodic bending of the finger joints is observed. When the fingers are periodically bent at different angles, regular electrical signals can be detected, indicating that the hydrogel sensor prepared in this invention has good responsiveness. Figure 8 This represents the change in relative resistance during periodic flexion of the wrist joint. Figure 9This represents the change in relative resistance during periodic flexion of the elbow joint. Figure 10 This represents the change in relative electrical resistance during periodic flexion of the cervical joint. Figure 11 This represents the change in relative electrical resistance during periodic flexion of the knee joint. (From...) Figure 7-11 It can be seen that the changes in the relative resistance curve of the sensor are basically consistent during multiple cycles of bending and straightening, indicating that the hydrogel sensor prepared by the present invention exhibits good repeatability. Figure 12 The change in relative resistance during periodic swallowing is shown. When periodic swallowing movements are performed, repetitive electrical signals can be clearly observed, indicating that the hydrogel sensor prepared in this invention can accurately monitor minute movements.

[0059] Based on the above examples and comparative examples, the following conclusions can be drawn: (1) The hydrogel provided by the present invention uses environmentally friendly crosslinking agent ethylene glycol dimethacrylate and prepares a chemically crosslinked network polyacrylic acid-based hydrogel electronic skin by free radical polymerization process. It overcomes the defects of low physical crosslinking efficiency and unstable network structure, and realizes efficient and controllable curing of hydrogel. The resulting hydrogel electronic skin has excellent mechanical properties and fatigue resistance. Its tensile strength reaches 1.798 MPa and its elongation at break reaches 700%. After 10 cycles of cyclic stretching at 500% strain, the tensile strength can still reach 1.2 MPa.

[0060] (2) The hydrogel electronic skin provided by this invention introduces the strong electrolytes lithium bis(trifluoromethanesulfonylimide) and zinc trifluoromethanesulfonate into the hydrogel system, and utilizes Li + Zn 2+ The efficient ion transport network constructed by plasma synergistic migration and the high dissociation ability of sulfonic acid groups significantly improves conductivity, and the hydrogel electronic skin achieves a conductivity of 2.212 S / m at room temperature.

[0061] (3) The hydrogel electronic skin provided by the present invention has good antifreeze properties. The addition of ethylene glycol makes the conductivity of the electronic skin reach 1.659S / m at a low temperature of -30℃, while maintaining good flexibility, thus broadening its application range in low temperature environments.

[0062] Although the invention has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of the invention. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. The invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

[0063] In the description of this invention, terms such as "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," which indicate direction or positional relationships, are based on the directions or positional relationships shown in the accompanying drawings. These are used merely for ease of description and do not indicate or imply that the device or element must have a specific orientation, or be constructed and operated in a specific orientation; therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0064] Furthermore, it should be noted that, in the description of this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0065] The term "comprising" or any other similar term is intended to cover non-exclusive inclusion, such that a process, article, or apparatus / device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to those processes, articles, or apparatus / devices.

[0066] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after such changes or substitutions will all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a core-coated conductive hydrogel electronic skin, characterized in that, The preparation method includes: Lithium bis(trifluoromethanesulfonyl)imide was added to deionized water and ultrasonically dispersed to obtain a lithium bis(trifluoromethanesulfonyl)imide dispersion with a mass fraction of 58% to 62%. The antifreeze, acrylic acid solution and the lithium bis(trifluoromethanesulfonylimide) dispersion were mixed in a certain proportion and then ultrasonically dispersed to obtain a first mixture. A chemical cross-linking agent is added to the first mixture and stirred to dissolve, thus obtaining a second mixture. Add an initiator to the second mixture and stir until homogeneous to obtain the first prepolymer solution; The first prepolymer liquid is injected into a mold and heated in an oven to obtain the sensing core layer. Zinc trifluoromethanesulfonate was added to deionized water and ultrasonically dispersed to obtain a zinc trifluoromethanesulfonate dispersion with a mass fraction of 68% to 72%. The antifreeze, the acrylic acid solution, and the zinc trifluoromethanesulfonate dispersion were mixed in a certain proportion and then ultrasonically dispersed to obtain a third mixture. Add the chemical crosslinking agent to the third mixture, stir to dissolve, and obtain the fourth mixture. Add the initiator to the fourth mixture and stir until homogeneous to obtain the second prepolymer solution; The sensing core layer is placed in a mold, the second prepolymer liquid is injected into the mold, and the mold is heated in an oven to obtain the core-encapsulated conductive hydrogel electronic skin.

2. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, The antifreeze is ethylene glycol, the chemical crosslinking agent is ethylene glycol dimethacrylate, the initiator is potassium persulfate, and the mass fraction of the acrylic acid solution is 54% to 56%.

3. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, In the step of mixing the antifreeze, acrylic acid solution and lithium bis(trifluoromethanesulfonyl)imide dispersion in a certain proportion, the mass ratio of the antifreeze, acrylic acid solution and lithium bis(trifluoromethanesulfonyl)imide dispersion is 1:2.7:(0.3-1.5).

4. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, In the step of adding a chemical crosslinking agent to the first mixture, the amount of the chemical crosslinking agent added is 0.05% to 0.15% of the first mixture; in the step of adding an initiator to the second mixture, the amount of the initiator added is 0.05% to 0.15% of the first mixture.

5. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, In the step of injecting the first prepolymer liquid into a mold and heating it in an oven to obtain the sensing core layer, the oven temperature is 65°C and the heating time is 1 hour, so that the thickness of the sensing core layer after heating is 1.2 mm to 1.4 mm.

6. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, In the step of mixing the antifreeze, the acrylic solution and the zinc trifluoromethanesulfonate dispersion in a certain proportion, the mass ratio of the antifreeze, the acrylic solution and the zinc trifluoromethanesulfonate dispersion is 1:3.5:(0.5-1.2).

7. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, In the step of adding the chemical crosslinking agent to the third mixture, the amount of the chemical crosslinking agent added is 0.03% to 0.06% of the mass of the third mixture; in the step of adding the initiator to the fourth mixture, the amount of the initiator added is 0.05% to 0.1% of the mass of the third mixture.

8. The method for preparing the core-encapsulated conductive hydrogel electronic skin according to claim 1, characterized in that, In the step of placing the sensing core layer into a mold, injecting the second prepolymer liquid into the mold, and heating it in an oven to obtain the core-coated conductive hydrogel electronic skin, the oven temperature is 80°C and the heating time is 2 hours, so that the thickness of the electronic skin obtained after heating is 2 mm to 2.3 mm.

9. The application of a core-coated conductive hydrogel electronic skin as a sensor, characterized in that, The electronic skin is prepared by the preparation method described in any one of claims 1 to 8.